Synthesis, spectral characterization, and in vitro anticancer evaluation of novel Flavanone-arylhydrazone derivatives - Reena Singh; Yogesh Murti (Journal of Applied Pharmaceutical Research, 2026)
Background: Flavanones are naturally occurring scaffolds with diverse pharmacological activities, including anticancer potential. Structural modification through hydrazone incorporation may enhance their biological properties and support the development of new therapeutic leads for breast cancer. Methodology: A series of nine flavanone-arylhydrazone derivatives was synthesized via condensation of substituted flavanones with phenylhydrazines under reflux conditions. The structures were confirmed using IR, ¹H NMR, and high-resolution mass spectrometry (HRMS). The compounds were evaluated for in vitro cytotoxicity against MCF-7 and MDA-MB-231 breast cancer cell lines using the MTT assay, with tamoxifen as the reference drug. Results and Discussion: All synthesized compounds exhibited dose-dependent cytotoxicity. Derivatives bearing electron-withdrawing substituents, such as nitro and halogen groups, showed relatively enhanced activity. Compounds 3 and 1 demonstrated the lowest IC₅₀ values (33–44 µM), indicating comparatively higher potency within the series. However, only modest differences in activity were observed among derivatives, suggesting that electronic effects alone do not fully govern cytotoxicity. Conclusion: Flavanone-arylhydrazone hybrids represent a promising scaffold for anticancer drug development. While electron-withdrawing substituents contribute to activity, the overall structure–activity relationship appears to be influenced by multiple physicochemical factors. Further mechanistic and in vivo studies are required to establish their therapeutic potential.